Luciano José Cabral Duarte e as ressonâncias do Concílio Vaticano II, em Sergipe (1962-1971) - Silva, Eduardo Augusto Santos (2017)
The Catholic Church summoned ecumenical councils since the early days of Christianity. These assemblies bring together Christian bishops from around the world to discuss problematic issues for the institution. At the Second Vatican Ecumenical Council (1962- 1965), it officialized its change of position with regard to the questioning of the modern, increasingly urban, industrial and secularized society of the twentieth century, which progressively renounced living the moral of Judeo-Christian origin. In Brazil, and especially in Sergipe, we analyze the impact of the diffusion of these modern values throughout the first half of the twentieth century, stimulated by the mass media, such as radio. In this context, the Sergipe population received the announcement that Pope John XXIII would hold a new Ecumenical Council in the Vatican in Rome. The purpose of John XXIII was to promote a renewal (aggiornamento) in the Catholic Church through dialogue with modernity and also to seek a rapprochement with the dissident Christian groups of Roman Catholicism. The then priest Luciano José Cabral Duarte, although not yet a bishop, followed that event in his own way, as a reporter for the national circulation magazine, O Cruzeiro and the newspaper aracajuano, A Cruzada. Thus he described the main activities of the Council and through his texts a great number of Brazilians had access to the main discussions of the Second Vatican Council. In 1966, Luciano Duarte was appointed auxiliary bishop of the Archdiocese of Aracaju, in the administration of Dom José Távora. In fulfilling this function, it was also up to the then Don Luciano to help in the process of implementing the conciliar guidelines in Sergipe. Thus, the main objective of this research is to discuss the Second Vatican Council as a historical event of significant impact in the modern society of the Western world and specifically in Brazil during the twentieth century. In addition, to investigate the effects of the conciliar guidelines in / and for Sergipe, through the study of part of the life trajectory of Luciano Duarte, both as journalist correspondent during the Second Vatican Council (1962- 1965) and as auxiliary bishop of the archdiocese of Aracaju (1966-1971).